Crime Prediction and Analysis Using Machine Learning - Rajasekhar Nennuri , Prathyusha Malyala , SaiTejaswi Thotakura , RajuTalari (International Journal of Advanced Science and Technology, 2020)
Crime is one of the largest and most daunting threats facing our general population and its preparation is a big one.